PENGARUH KEBERADAAN ANGKUTAN BERBASIS ON-LINE TERHADAP KESADARAN HUKUM KONSUMEN - Marsitiningsih, Marsitiningsih (Solusi, 2017)
The existence of on-line transport is the answer to the public's complaints about the current conventional transport conditions. The development of online transportation services is much more beneficial to the consumer community because of the ease of access and a much more transparent and targeted system. Although the existence of this online transportation service threatens the existence of conventional transportation, but consumer choice remains on the online transport. Online transport has created a legal awareness of the community / consumers that is aligned with the objectives of consumer protection.